Recent Advances in the Pathogenesis of Syndromic Autisms - A. Benvenuto; B. Manzi; R. Alessandrelli; C. Galasso; P. Curatolo (Hindawi Limited, 2009)
Background. Current advances in genetic technology continue to expand the list of medical conditions associated with autism. Clinicians have to identify specific autistic-related syndromes, and to provide tailored counseling. The aim of this study is to elucidate recent advances in autism research that offer important clues into pathogenetic mechanisms of syndromic autism and relevant implications for clinical practice. Data Sources. The PubMed database was searched with the keywords "autism" and "chromosomal abnormalities," "metabolic diseases," "susceptibility loci." Results. Defined mutations, genetic syndromes, and metabolic diseases account for up to 20% of autistic patients. Metabolic and mitochondrial defects may have toxic effects on the brain cells, causing neuronal loss and altered modulation of neurotransmission systems. Alterations of the neocortical excitatory/inhibitory balance and perturbations of interneurons' development represent the most probable pathogenetic mechanisms underlying the autistic phenotype in Fragile X-Syndrome and Tuberous Sclerosis Complex. Chromosomal abnormalities and potential candidate genes are strongly implicated in the disruption of neural connections, brain growth, and synaptic/dendritic morphology. Conclusion. Metabolic testing may be appropriate if specific symptoms are present. High-resolution chromosome analysis may be recommended if a specific diagnosis is suspected because of obvious dysmorphisms. Identifying cryptic chromosomal abnormalities by whole genome microarray analysis can increase the understanding of the neurobiological pathways to autism.